Incidence of Periodontal Attachment Loss over 8 to 10 Years among Iowa Elders Aged 71+ at Baseline - Fang Qian, PhD; Steven M. Levy, DDS, MPH; John J. Warren, DDS, MS; (Blackwell Synergy, 2007)
There has been limited research on the long-term incidence of periodontal attachment loss (ALOSS) among adults aged 70 and older.